(untitled) (Journal of Astronomy & Earth Sciences Education, 2016)
Although traditional lectures are still the dominant form of undergraduate instruction, there have been relatively few studies comparing various learner-centered and active learning teaching strategies to one another in order to guide professors in making informed instructional decisions. To study the impact of different active learning approaches, pre-test to posttest learning gains for students receiving instruction on introductory astronomy solar system topics through a combination of collaborative learning activities and formative assessment-driven activities were compared to the gains of students being taught the same topics by traditional lectures only. After traditional lectures, students improved from a pre-test score of 42% (n=144) to 49% (n=49). After lecture tutorials and classroom voting response systems improvement was to 73% (n=72) Using a multiple-group comparison approach, similar earning gains were also observed when using visual-assessment and tutorial activities. Moreover, data from a Likert-style attitude survey of 264 undergraduates showed that, although they did not report a clear preference for one instructional mode over the other, the majority of students believed that the active and collaborative nature of the activities helped them learn. The results of this study add weight to the notion that most modern pedagogies are superior to traditional lecture, and that although the relative impacts of particular pedagogies are mostly indistinguishable from one another, they are all are better than traditional lecture alone.